'Turn‐on' fluorescence sensing of hydrogen peroxide in marine food samples using a carbon dots–MnO2 probe. (11th March 2020) - Ning, Keke; Xiang, Guoqiang; Wang, Cuicui; Huang, Feihong; Liu, Jinzhi; Zhang, Lanlan; Yan, Minmin; Hu, Bingqian; Lei, Wen
Abstract: A 'turn‐on' fluorescence method for detection of hydrogen peroxide (H2 O2 ) in marine food samples is presented in this article. Using this method, a carbon dots (CDs)–MnO2 probe was formed in which fluorescence intensity (FI) of CDs was quenched through fluorescence resonance energy transfer by addition of MnO2 nanosheets. When H2 O2 was added into the CDs–MnO2 solution, the MnO2 nanosheets formed Mn 2+ ions due to a redox reaction between H2 O2 and MnO2 nanosheets, and CD FI was recovered. Under optimized conditions, the detection limit for H2 O2 was 0.87 μM, and analytical linear range was 4–100 μM. Furthermore, this developed fluorescence sensing system was successfully used with satisfactory results to determine trace H2 O2 content in marine food samples.